MEDICAL AND SOCIAL PECULIARITIES OF ORTHOPEDIC PATHOLOGY FORMING IN PRE-SCHOOL CHILDREN - S.N. Simanova; I.V. Kirgizov; R.N. Terletskaya (Вопросы современной педиатрии, 2010)
(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(1):177-178)